Automated red blood cell exchange in preparation for filgrastim mobilization of autologous peripheral blood hematopoietic progenitor cells in a patient with sickle cell anemia. Issue 3 (11th November 2017) - Zhao, Yong; Bailey, Jeffrey A.; Linden, Jeanne; St. Pierre, Patricia; Cerny, Jan; Vauthrin, Michelle; Greene, Mindy; Weinstein, Robert
Abstract : Increasing survival of patients with sickle cell anemia (SCA) well into adulthood results in a rising likelihood of developing hematological malignancy. High‐dose chemotherapy with autologous hematopoietic progenitor cell (HPC) rescue is standard of care for several hematological malignancies, but the risk of severe or life‐threatening vaso‐occlusive phenomena during filgrastim mobilization of HPC for collection poses a potential barrier to this approach. We report the use of automated red cell exchange in preparation for filgrastim mobilization in a patient with homozygous SCA. Red cell exchange was repeated just prior to high‐dose chemotherapy to mitigate the need for red cell transfusion during bone marrow reconstitution. The patient experienced no vaso‐occlusive phenomena throughout the entire episode of care and did not become iron overloaded. This approach should be considered for all patients with homozygous or compound heterozygous sickle cell disease who are candidates for auto‐HPC rescue therapy.